Cystectomy vs. bladder preservation after neoadjuvant chemotherapy in muscle-invasive bladder cancer: A tertiary medical center experience. (2020) - Halabi, Ibrahim El; Husseini, Ziad El; Haibe, Yolla; Charafeddine, Maya; Mukherji, Deborah; Temraz, Sally; Bulbul, Muhammad; Khauli, Raja; Nasr, Rami; Wazzan, Wassim; Hajj, Albert El; Geara, Fady; et al.
Highlights: No difference in OS and DFS between radical cystectomy and chemoradiation post-neoadjuvant chemotherapy. Possibility of bladder preservation post neoadjuvant chemotherapy. Pathologic T stage at diagnosis affects prognosis regardless of treatment modality. Abstract: Background: Radical cystectomy (RC) remains the standard of care for muscle-invasive bladder cancer (MIBC). Because of the higher overall risks associated with RC, particularly in the elderly patients with multiple comorbidities, other less invasive bladder preservation strategies have been considered. Methods: This is a retrospective chart review of patients diagnosed with MIBC, pT2–4N0–2M0, at the American University of Beirut Medical Center between 2007 and 2017. Results: 98 patients, 85 (86.7%) males and 13 (13.3%) females, were included. Of the 98 patients, 19 (19.3%) patients were treated with upfront CRT, 35 (35.7%) were treated with upfront RC and 44 (45%) were treated with NAC. 26 (26.5%) patients underwent RC after NAC and 18 (18.4%) received CRT after NAC. The mean overall survival (OS) for the different treatment modalities was 69.4, 60.4, 56.1 and 44.2 months for RC, CRT, RC post-NAC and CRT post-NAC, respectively ( p  = 0.83). The median disease-free survival (DFS) was 29, 22, 21 and 16 months for RC, CRT, RC post-NAC and CRT post-NAC, respectively ( p  = 0.49). Patients with pT3/T4 had a higher risk of death by 3.335 folds compared to pT2 (95% CI [1.321–8.422], p <0.05). Conclusions: No difference was noted in the OS and DFS between the groups who underwent RC post-NAC and CRT post-NAC. These findings further support the possibility of bladder preservation after the treatment with NAC for MIBC. The pathologic T stage at diagnosis is an important prognostic factor regardless of treatment modality.